348 WHAT IS THE OLDER PATIENT'S VIEW ON RECEIVING DETAILED MEDICAL LETTERS?. (25th October 2022) - Butler, E; Walsh, JE; Grogan, S; Lyons, C; Whalley, D; Fitzpatrick, J; Gallagher, L; Dockery, F
Abstract: Background: Sending copies of clinic letters to patients involves additional work for medical staff in formatting letters, administrative staff in printing and posting and is an added cost to the healthcare service. Though seen largely as good practice in some specialities, it is not done routinely in Geriatric medical services. We introduced this practice as standard in our service and wished to evaluate whether from the patient perspective, it is worthwhile. Methods: We sent a questionnaire to n=80 older patients who were evaluated in the home setting (by the Integrated Care Team for Older People – ICTOP) or recently attended CGA (Comprehensive Geriatric Assessment) clinic or FLS (Fracture Liaison Service) clinic. We asked their opinion on the detailed medical letter sent to their General Practitioner (GP), which they received a copy of. The questionnaire could be completed by patient/carer/relative, and returned anonymously. Results: N=30/80 were returned. Two said they found the letter difficult to understand; 1/30 said the letter caused them to worry but all said they still preferred that they had received it. N= 2 said they would like to have contributed to the letter for accuracy. All said they felt they should receive copies of all their medical correspondence. Free text comments showed overwhelming support for the process, in allowing them to self-manage their health, enhance communication with other healthcare professionals and was a useful document to refer back to when they are trying to process information during short consultations. Conclusion: Though a small survey and limited by low response rate, older people expressed high levels of satisfaction in receiving copies of medical letters about their health. It supports the ongoing practice and should be adopted widely.